DIVERSITY AND INCLUSION WITHIN MULTICULTURAL LEADERSHIP IN THE COVID YEARS: A BIBLIOMETRIC STUDY 2019-2022 - Constantin Bratianu; Dan Paiuc (Oradea Journal of Business and Economics, 2023)
According to Harvard Business Review, companies with higher diversity experienced 19% higher revenues, but in the meantime, 57% of employees feel their businesses must assiduously concentrate on diversity and inclusion plans. This article aims to present a bibliometric study of diversity and inclusion (DI) in the COVID years 2019-2022. Our analysis was based on the Scopus database, while the bibliometric research was performed via VOSviewer: version 1.6.17, one of the most utilized academic software tools for constructing and visualizing bibliometric networks. In conclusion, our research questions are answered, underlining that, during the last 4 COVID years 2019-2022 the DI phenomenon was a main vector of multinational leadership (ML) and that physical/mental abilities, race and ethnicity, and educational background are the new main drivers of DI. The value of these findings resides in the agile repositioning of the DI role within multinational leadership and can serve as a reference and guidance both for business professionals and researchers.